2021
DOI: 10.3390/ijerph18073481
|View full text |Cite
|
Sign up to set email alerts
|

Higher Accuracy of Lung Ultrasound over Chest X-ray for Early Diagnosis of COVID-19 Pneumonia

Abstract: Background: The COVID-19 pandemic rapidly strained healthcare systems worldwide. The reference standard for diagnosis is a positive reverse transcription polymerase chain reaction (RT-PCR) test, but results are not immediate and sensibility is variable. Aim: To evaluate the diagnostic accuracy of lung ultrasound compared to chest X-ray for COVID-19 pneumonia. Design and Setting: A retrospective analysis of symptomatic patients admitted into one primary care centre in Spain between March and September 2020. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…Finally, in our study, patients most frequently presented fever, followed by cough, as reported in other studies [4,5,17,19]. The LUS findings of our study are similar to those shown in other studies [7][8][9][10][11][12][13][14]18].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Finally, in our study, patients most frequently presented fever, followed by cough, as reported in other studies [4,5,17,19]. The LUS findings of our study are similar to those shown in other studies [7][8][9][10][11][12][13][14]18].…”
Section: Discussionsupporting
confidence: 92%
“…The capacity of LUS for early detection of COVID-19 pneumonia was already described in other publications [ 10 , 17 , 23 ]. Here, for the first time in primary care, we show the great relevance of LUS to predict the evolution of COVID-19 pneumonia diagnosed by ultrasound and confirmed by biological tests.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…As a result, our LUS score values were higher than those in previous publications, which included patients being admitted to emergency departments or general wards, in their initial stages of the disease. (13) In addition, we decided to include the lung lateral region to the axilla and to the PLAPS points, where pleural effusion and larger consolidations are usually observed. The pleura is not described in detail because although it was found to be altered (pleural disruption, pleural thickening), the transducer was intended for the assessment of type A, type B lung patterns, and subpleural consolidations and in the PLAPS points.…”
Section: /7mentioning
confidence: 99%
“…(5) Several studies have shown that LUS can detect interstitial disease, subpleural consolidations, and respiratory distress of any aetiology, with sensitivity and specificity superior to chest radiography and comparable to CT. (6)(7)(8) Indeed, LUS has already been recommended in past viral pandemics (9) and growing evidence demonstrates its effectiveness in patients with COVID-19, (10) which allows identifying the degree of lung involvement, its course, and the possible association between the initial lung involvement and its prognosis. (11)(12)(13)(14)(15) Our objective was to evaluate the performance of LUS through the lung ultrasound score (LUS score) to determine the severity of pneumonia and the short-term outcomes of patients with COVID-19 admitted to the intensive care unit. We hypothesize that the Lung Ultrasound Score (LUS) correlates with clinical evolution and predicts mortality in critically ill COVID-19 pneumonia patients.…”
Section: Introductionmentioning
confidence: 99%